2012
DOI: 10.1371/journal.pone.0049309
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Has Greatly Elevated Mismatch Tolerance at 3′-UTR Sites

Abstract: It has been noted that target sites located in the coding region or the 3′-untranslated region (3′-UTR) can be silenced to significantly different levels by the same siRNA, but little is known about at what specificity the silencing was achieved. In an exploration of positional effects on siRNA specificity by luciferase reporter system, we surprisingly discovered that siRNA had greatly elevated tolerance towards mismatches in target sites in the 3′-UTR of the mRNA compared with the same target sites cloned in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Anyhow, it didn't alter its ability to trigger RNA cleavage as showed by decreased levels of HTT mRNA in both models. Nevertheless, we can't exclude that part of this effect is mediated by translational repression or mRNA decay mediated by Ago1, 3 and 4 as previously demonstrated [40] , [41] .…”
Section: Discussionmentioning
confidence: 75%
“…Anyhow, it didn't alter its ability to trigger RNA cleavage as showed by decreased levels of HTT mRNA in both models. Nevertheless, we can't exclude that part of this effect is mediated by translational repression or mRNA decay mediated by Ago1, 3 and 4 as previously demonstrated [40] , [41] .…”
Section: Discussionmentioning
confidence: 75%
“…A literature vector ( 24 ) was employed as a reporter of miRNA by inserting the potential target sequence in frame to form fused reporter gene with the target site located in the coding region. The inhibitory effect of miRNA on the target sequence represented the effectiveness of miRNA recognizing the target.…”
Section: Methodsmentioning
confidence: 99%
“…The 5′ end of the gene was chosen to minimize the chances of off-target effects, for the following reasons: (1) it is distal from the region of 3′ overlap with the adjacent At2g19340 gene; (2) it is from a unique sequence region, sharing only 66% nucleotide sequence identity with PIRL7; and (3) the longest continuous stretch of alignment with any other predicted transcripts is only 9 bp, well below the similarity threshold required to trigger off-target RNAi. Furthermore, the RNAi pathway has considerably less tolerance for target sequence mismatches in 5′ coding sequences than in 3′ untranslated regions (Wei et al, 2012). A second construct, PIRL6-KD(L), with inverted repeats of the 5′-most 458 nucleotides of the coding region, also was produced.…”
Section: Pirl6 Knockdown Disrupts Gametophyte Developmentmentioning
confidence: 99%
“…It is unlikely that the observed consistent gametophyte dysfunction resulted from nonspecific or transformation-related effects. The inverted repeat constructs used in these experiments were designed to maximize specificity in two ways: by incorporating a region of PIRL6 that lacks extended sequence homology with other PIRLs and by targeting the 5′ end of the mRNA, where the RNAi pathway is less tolerant of mismatches between small interfering RNAs and target sequence (Wei et al, 2012). More importantly, knockout mutations in PIRL7 and PIRL8, the two genes most closely related to PIRL6, have been identified (Forsthoefel et al, 2005;Chen et al, 2010b), and they do not result in reproductive defects resembling those reported here for PIRL6.…”
Section: Pirl6 Knockdownmentioning
confidence: 99%